2011
DOI: 10.1192/apt.bp.109.006916
|View full text |Cite
|
Sign up to set email alerts
|

EEG in psychiatric practice: to do or not to do?

Abstract: SummaryElectroencephalography (EEG) is a non-invasive investigation that can aid the diagnosis of psychiatric and neuropsychiatric disorders. A good predictor of an abnormal EEG recording is the presence of an organic factor identified during the clinical assessment. The non-invasiveness and low cost of the procedure and its ability to measure spontaneous brain activity appear to attract clinicians to utilise this investigative tool. However, studies have reported that EEGs arising from psychiatric referrals h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…These data proved interesting in that a power was significantly increased after intra-PFC DHK treatment. This finding is consistent with results observed in depressed patients, in whom a power is increased with illness and normalized with antidepressant treatment (for review, see Badrakalimuthu et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These data proved interesting in that a power was significantly increased after intra-PFC DHK treatment. This finding is consistent with results observed in depressed patients, in whom a power is increased with illness and normalized with antidepressant treatment (for review, see Badrakalimuthu et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
“…These results suggest that significant global impairments of cortical activity do not result from DHK treatment. Human studies have shown that patients with MDD display increased power in the a frequency range (9-13.5 Hz) during quiet wakefulness, which is gradually reversed in the course of antidepressant treatment (for review, see Badrakalimuthu et al, 2011). We therefore calculated the relative power in the d (1-4.5 Hz), y (5-8.5 Hz), a (9-13.5 Hz), b (14-31.5 Hz), and lower g (32-58 Hz) frequency ranges and compared these values between vehicle and DHK injections.…”
Section: Effects Of Dhk On Eegmentioning
confidence: 99%
“…Yet, EEG studies typically suffer from poor spatial resolution with a relatively imprecise location of electromagnetic patterns associated with the neural current flow [38]. Notwithstanding, the low cost of the examination and its great ability to measure spontaneous brain activity seem to attract professionals to use this tool [21]. The high density of the EEG, combined with TMS, provides a direct and non-invasive measure of cortical excitability and connectivity in humans.…”
Section: Advantages and Disadvantagesmentioning
confidence: 99%
“…The neurons generate small electrical currents around cell membranes, specifically along the dendrites, and they receive input signals from other neurons [22]. These electrical activities result from the electrochemical communication among neurons and correspond to the information flow occurring in several cortical regions [21]. The EEG allows monitoring, identifying and classifying electrophysiological bioelectrical signals in frequency ranges, bands of activity, or brain rhythms, relating them to waking and non-waking states [23].…”
Section: Electroencephalographymentioning
confidence: 99%
See 1 more Smart Citation